Pengaruh Likuidasi Bank Terhadap Perlindungan Para Nasabah (Studi Kasus BPR Legian Denpasar) - Nazhif Ali Murtadho; Millatus Shohihah (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2024)
Financial institutions, one of which is a bank or a place to store funds for the community. Banking institutions have a very important role in people's lives, but it does not rule out the possibility that banks can commit several violations that could result in losses for customers. In this case, there are various forms of violations such as misuse of customer funds, as is the case with the Denpasar regional bank, specifically in the Legian area. The bank is called Legian People's Credit Bank (BPR). Because BPR Legian did not reach the Capital Adequacy Ratio (CAR) because BPR Legian had used customer money for extravagance. The purpose of this writing is to find out the meaning of bank liquidation, the legal basis for liquidated banks, the consequences of revoking a bank's business license, protection of BPR Legian customers, and also to analyze cases that occurred at the Legian People's Credit Bank, Denpasar. This research uses a normative method with a case study approach, and is supplemented by using secondary legal materials with primary materials as the main source in this research in the form of Law Number 24 of 2004 concerning the Deposit Insurance Corporation, and secondary materials including legal journals and several literatures. related to this research. BPR Legian was liquidated due to poor debt management which had experienced extreme leverage or a situation where the amount of debt was above the assets of the company or bank.